2016
DOI: 10.14260/jemds/2016/939
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study Comparing Tamsulosin and Silodosin in Medical Expulsive Therapy for Lower Ureteric Stones

Abstract: The urinary stone disease is one of the most common afflictions of the modern society and it has been described since antiquity with the westernization of global culture. The efficacy of mini-invasive therapies, such as Extracorporeal Shock Wave Lithotripsy [ESWL] and ureteroscopy are not risk free, are problematic and are quite expensive. Recently, the use of watchful waiting approach has been extended by using Pharmacotherapy. This can reduce symptoms and facilitate stone expulsion. MATERIALS AND METHODSThi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…One study [ 28 ] had a high risk of attrition bias (incomplete outcome data). Seven studies [ 21 , 22 , 27 29 , 31 , 32 ] were rated as having a high risk of bias due to no prespecified sample size calculation. Three observational studies [ 33 35 ] were identified, and the quality of these studies was high (NOS score: 9).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…One study [ 28 ] had a high risk of attrition bias (incomplete outcome data). Seven studies [ 21 , 22 , 27 29 , 31 , 32 ] were rated as having a high risk of bias due to no prespecified sample size calculation. Three observational studies [ 33 35 ] were identified, and the quality of these studies was high (NOS score: 9).…”
Section: Resultsmentioning
confidence: 99%
“…A subgroup analysis showed that the expulsion rate changed with stone size and study design and was not influenced by the follow-up time (1, 2, 3, or 4 weeks) or stone location (only DUSs or not only DUSs) ( Table 3 ). For stone sizes, silodosin had a significantly higher expulsion rate than tamsulosin in patients with stone sizes of 5~10 mm (five studies [ 18 , 26 , 29 , 31 , 34 ], n = 410, pooled RD: 0.14, 95% CI: 0.06 to 0.22, I 2 = 0%). However, silodosin had no superior effect over tamsulosin for stone sizes of <5 mm (three studies [ 26 , 31 , 34 ], n = 150, pooled RD: 0.03, 95% CI: -0.06 to 0.11, I 2 = 0%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the incidence of retrograde ejaculation was considerably higher in the silodosin group. [11][12][13][14][15][16][17][18][19][20][21][22][23][24] Alpha-adrenergic receptors are observed throughout the human ureter, predominantly in the distal ureter. 25 Stimulation of these receptors increases the force of contraction of the ureter and the ureteral peristaltic frequency.…”
Section: Discussionmentioning
confidence: 99%